Improving students’ problem-solving skills through RIAS model in science classes - Ahmad Muhlisin; Sri Sarwanti; Gentur Jalunggono; Arnanda Yusliwidaka; Sukron Mazid; Lilia Ellany Mohtar (LPMPP Universitas Negeri Yogyakarta, 2022)
Learning has indisputably been hampered throughout the Coronavirus 2019 pandemic, as perceived in undesirable observed phenomena such as students’ ennui, learning loss, poor engagement, poor problem analysis skill, and inability to properly provide solutions to various predicaments. In view of this, the present study aimed to examine the effect of the Reading, Identification, Analysis, and Self-reflection (RIAS) learning model implemented in online learning to improve students' problem-solving skills. It was quasi-experimental research with a pretest and posttest control group design involving 60 undergraduate students in a general biology course. They were divided into two groups each of which consisted of 30 students, as the control and experimental class. The control class harnessed the lecture method while the experimental one executed the RIAS model. To collect the data, this study used an essay test consisting of 20 items with a reliability level of 0.886, and the figures were later scrutinized by means of descriptive and ANCOVA analysis. The results revealed that the RIAS model with reading, identification, analysis, and self-reflection techniques had a considerable impact on problem-solving skills, as evidenced by the mean score difference of 33.06 (low) and 66.33 (very high) between the lecturing and RIAS groups. The findings recommend that educators should simulate the RIAS model before online learning so that the learning activities can run as planned and that students can be more focused on the discussions of the learning topics. A further study could improve the quality of student activities at each stage of learning and develop teaching materials to support the RIAS learning model for a more qualified teaching-learning process and outcome.